Loss‐of‐function desmoplakin I and II mutations underlie dominant arrhythmogenic cardiomyopathy with a hair and skin phenotype. (2nd January 2019) - Maruthappu, T.; Posafalvi, A.; Castelletti, S.; Delaney, P.J.; Syrris, P.; O'Toole, E.A.; Green, K.J.; Elliott, P.M.; Lambiase, P.D.; Tinker, A.; McKenna, W.J.; Kelsell, D.P.
Summary: Background: Arrhythmogenic cardiomyopathy (AC) is an inherited, frequently underdiagnosed disorder, which can predispose individuals to sudden cardiac death. Rare, recessive forms of AC can be associated with woolly hair and palmoplantar keratoderma, but most autosomal dominant AC forms have been reported to be cardiac specific. Causative mutations frequently occur in desmosomal genes including desmoplakin ( DSP ). Objectives: In this study, we systematically investigated the presence of a skin and hair phenotype in heterozygous DSP mutation carriers with AC. Methods: Six AC pedigrees with 38 carriers of a dominant loss‐of‐function (nonsense or frameshift) mutation in DSP were evaluated by detailed clinical examination (cardiac, hair and skin) and molecular phenotyping. Results: All carriers with mutations affecting both major DSP isoforms (DSPI and II) were observed to have curly or wavy hair in the pedigrees examined, except for members of Family 6, where the position of the mutation only affected the cardiac‐specific isoform DSPI. A mild palmoplantar keratoderma was also present in many carriers. Sanger sequencing of cDNA from nonlesional carrier skin suggested degradation of the mutant allele. Immunohistochemistry of patient skin demonstrated mislocalization of DSP and other junctional proteins (plakoglobin, connexin 43) in the basal epidermis. However, in Family 6, DSP localization was comparable with control skin. Conclusions: This study identifies a highly recognizable cutaneous phenotype associated with dominant loss‐of‐function DSPI/II mutations underlying AC. Increased awareness of this phenotype among healthcare workers could facilitate a timely diagnosis of AC in the absence of overt cardiac features. Abstract : What's already known about this topic? The diagnosis of the early phases of arrhythmogenic cardiomyopathy (AC) remains challenging. AC is linked to mutations in desmosomal genes including desmoplakin ( DSP ). Desmosomes have key functions in the heart, skin and hair, highlighted by rare predominantly recessively inherited DSP mutations linked to 'woolly' hair, keratoderma and severe cardiomyopathy in childhood. What does this study add? The presence of curly hair and keratoderma is likely to be a useful additional clinical identifier of autosomal dominant patients with AC associated with DSPI/II mutations. Haploinsufficiency is the underlying genetic mechanism. Immunohistochemistry of patient skin demonstrated mislocalization of DSP and other junctional proteins (plakoglobin, connexin 43) in the basal epidermis. What is the translational message? Here, we show that dominant AC‐associated loss‐of‐function DSP mutations can also be linked to curly hair and mild palmoplantar keratoderma. These cutaneous features could therefore provide clinical clues enabling early diagnosis and directed family screening, especially in the subtle early phases of AC. Linked Comment:  Ramot. Br J Dermatol 2019; 180 :983–984 . Plain language summary available online Respond to this article